The Role of Young Doctors' Health Parliament as an effective policy tool in Tackling NCDs: An innovative approach - Karthikeyan, Venkatesh; Bera, Omprakash; Kumar, Chandan; Joshi, Krupal; Venkatesh, U; Dalui, Anirban; Hariharan, VS; Hasan, Abul K M; Srinivasan, Shiva Prakash (Indian Journal of Community Health, 2024)
Non-communicable diseases (NCDs) are increasingly recognized as a severe public health concern threatening the human race, development, and quality of life. In the last three decades, Years of healthy life lost due to disability (YLD) has witnessed a significant shift from Communicable diseases towards NCDs and injuries (1). Globally, the economic burden of NCDs is projected to rise to over 13 trillion dollars by the year 2030, and every 10% hike in NCDs is expected to cause a 0.5% decline in global economic growth(2). The poor and disadvantaged population is disproportionately affected by NCDs, contributing to increased health disparities within and between nations (3). In low- and middle-income countries like India, NCDs are expected to diminish their GDP by 1% to 5% annually(3). The novel concept of the Young Doctors' Health Parliament (YDHP) is uniquely positioned to leverage the fresh perspectives and energetic engagement of young medical professionals who are at the forefront of encountering and managing NCDs. This article explores how the Young Doctors' Health Parliament serves as a pivotal mechanism for young doctors to influence health policy, thereby playing a crucial role in mitigating the NCD burden that disproportionately affects their peers and younger generations.